2019
DOI: 10.1016/j.colsurfa.2019.123862
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a new mass-concentration, chain-reaction model with the population-balance model for early- and late-stage aggregation of shattered graphene oxide nanoparticles

Abstract: Comparison of a new massconcentration, chain-reaction model with the population-balance model for early-and late-stage aggregation of shattered graphene oxide nanoparticles. Colloids and Surfaces A: Physicochemical and Engineering Aspects, 582, p. 123862.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…Also, the available mathematical models that try to couple the transport equation with an expression for aggregation (Babakhani et al., 2018; Chatterjee & Gupta, 2009; Quik et al., 2015; Raychoudhury et al., 2012; Taghavy et al., 2015) may provide improved results, but either they do not take into account for appropriate particle dispersion or they fail to account for the existence of repulsive forces between charged particles. Other models use simplifying or empirical reaction rates (Babakhani et al., 2019), and general attachment equations (Wang et al., 2018) to account for transport and aggregation of particles. The mathematical model developed by Babakhani (2019) takes into account transport and aggregation of nanoparticles and evaluates their size exclusion.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the available mathematical models that try to couple the transport equation with an expression for aggregation (Babakhani et al., 2018; Chatterjee & Gupta, 2009; Quik et al., 2015; Raychoudhury et al., 2012; Taghavy et al., 2015) may provide improved results, but either they do not take into account for appropriate particle dispersion or they fail to account for the existence of repulsive forces between charged particles. Other models use simplifying or empirical reaction rates (Babakhani et al., 2019), and general attachment equations (Wang et al., 2018) to account for transport and aggregation of particles. The mathematical model developed by Babakhani (2019) takes into account transport and aggregation of nanoparticles and evaluates their size exclusion.…”
Section: Introductionmentioning
confidence: 99%
“…This finding lies in line with our previous statement [2], and experimental results obtained in previous studies [29], that reversible platelet aggregation is the process of destabilization of large aggregates formed in the first phase. Although in this study the dependence of the model parameters on ADP concentration was not observed, we expect the parameters k 1 and k 2 to be linearly proportional to the logarithm of reagent concentration as was described earlier by Babakhani et al [30].…”
Section: Discussionmentioning
confidence: 57%
“…Derived count rates (DCR), determined by dynamic light scattering (DLS), have been used as an indicator for the mass concentration of dispersed particles in suspensions. [30][31][32] Here we used the product of a DCR value (kcps) and the corresponding volume (mL) of suspension as the indicator of accumulative nanoprecipitation. The DCR of pure DMF-PBS mixture with no drug was regarded as the blank for subtraction.…”
Section: Effect Of Salt Concentration On Drug and Polymer Precipitationmentioning
confidence: 99%